Catalyst for preparing crotonaldehyde through ethanol dehydrogenation as well as preparation method and application of catalyst
By loading a copper-based catalyst onto a SiO2 support and introducing an auxiliary agent, a Cu-M/SiO2 catalyst was prepared, which solved the catalyst design problem in the one-step preparation of crotonaldehyde from ethanol. This achieved a highly efficient and selective conversion of ethanol to crotonaldehyde, simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202511936347.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-01-30
AI Technical Summary
In the existing technology, the catalyst for the one-step preparation of crotonaldehyde from ethanol has the problem of catalyst design, making it difficult to achieve the synergistic effect of multiple active centers such as dehydrogenation, condensation and dehydration. In addition, the traditional process is long, energy-intensive, has many side reactions, and has low product yield and purity.
A copper-based catalyst was supported on SiO2 and introduced with chromium, cerium, lanthanum, zirconium, zinc and other additives. The catalyst was prepared by sol-gel method and hydrothermal reaction, integrating dehydrogenation, condensation and dehydration active centers to form Cu-M/SiO2 catalyst, which is used for one-step conversion of ethanol to crotonaldehyde in a single reactor.
This method enables the efficient conversion of ethanol to crotonaldehyde in a single reactor, simplifying the process, reducing equipment investment and operating costs, and providing mild reaction conditions, high selectivity, few byproducts, and a stable and regenerable catalyst.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of catalytic synthesis, and particularly relates to a catalyst for preparing crotonaldehyde by dehydrogenation of ethanol as well as a preparation method and application thereof. BACKGROUND
[0002] Crotonaldehyde, also known as butenal, is an important organic chemical intermediate, which is widely used in the synthesis of butyraldehyde, butanol, sorbic acid, perfume, pesticide and rubber antioxidant, etc. The traditional industrial production method of crotonaldehyde mainly uses acetaldehyde as raw material to perform aldol condensation to generate 3-hydroxybutyraldehyde in the presence of an alkaline catalyst, and then performs dehydration to generate crotonaldehyde under acidic conditions. This process route is mature, but has obvious defects: firstly, the production of raw material acetaldehyde is seriously dependent on the petroleum route and is mainly prepared by ethylene oxidation method, which is greatly affected by the fluctuation of crude oil price; secondly, this process involves two independent steps of condensation and dehydration, has a long process flow, high energy consumption, and is prone to produce side reactions such as resinification, thereby affecting the product yield and purity.
[0003] Ethanol, as a renewable platform molecule, can be produced on a large scale through biomass fermentation in addition to the petroleum route, and is widely available and green and sustainable. Therefore, it is of important strategic significance and economic value to develop a new process for directly synthesizing crotonaldehyde from ethanol as raw material. In theory, this process involves multiple reactions such as dehydrogenation of ethanol to generate acetaldehyde, aldol condensation of acetaldehyde with ethanol (or another molecule of acetaldehyde), and dehydration and isomerization of the condensation product.
[0004] In the prior art, some researches have tried to combine photocatalysis with thermal catalysis to realize the conversion of ethanol to crotonaldehyde, such as patent CN112939752A. This method has mild reaction conditions, but has problems such as high requirement for light equipment, long reaction period and low efficiency, and still has a distance from industrial application. On the other hand, it is a more attractive research direction to develop a high-efficiency multifunctional thermal catalyst to realize one-step preparation of crotonaldehyde from ethanol in a single reactor. However, the core challenge of this technical route lies in the design of the catalyst: the catalyst needs to have multiple active centers such as dehydrogenation, condensation and dehydration, and realize the synergistic effect of these centers in the reaction process, while inhibiting side reactions such as excessive dehydrogenation to generate acetic acid, excessive dehydration to generate ethylene, or deep cracking to generate methane, carbon monoxide, etc.
[0005] Copper-based catalysts exhibit high activity in the reaction of ethanol dehydrogenation to acetaldehyde, but they are prone to sintering and deactivation at higher temperatures, and their catalytic ability for subsequent condensation and dehydration reactions is limited. Introducing appropriate additives and optimizing the support structure is an effective way to improve the performance of copper-based catalysts and expand their functions. For example, some patents (such as CN116162019A patent) report the use of CuSn catalysts for the production of acetaldehyde from ethanol, but the target product is acetaldehyde, and the conversion to crotonaldehyde is not involved. The presence of Sn can lead to the breaking of C-C bonds, which is not conducive to the growth of carbon chains to form crotonaldehyde. Therefore, the development of a new type of catalyst that can efficiently catalyze the one-step synthesis of crotonaldehyde from ethanol with high selectivity and stability is of great significance for simplifying the process, improving product selectivity, and promoting industrial applications. SUMMARY
[0006] To solve the problems mentioned in the background art, the purpose of the present application is to provide a catalyst for the preparation of crotonaldehyde from ethanol dehydrogenation and its preparation method and application. The active component copper and the additive metal are supported on SiO2 carrier, successfully realizing the one-step conversion of ethanol to crotonaldehyde in a single reactor, greatly simplifying the process flow and reducing equipment investment and operating costs.
[0007] The purpose of the present application can be achieved by the following technical solutions:
[0008] A catalyst for the preparation of crotonaldehyde from ethanol dehydrogenation, the catalyst comprising a SiO2 carrier, the SiO2 carrier supporting an active component and an additive metal, the active component being copper, the additive metal being one or more of chromium, cerium, lanthanum, zirconium, and zinc, the mass fraction of the SiO2 carrier being 70-89.5%, the mass fraction of the active component being 10-25%, and the mass fraction of the additive being 0.5-5%. The catalyst is prepared by a sol-gel method using copper nitrate, nitrate additive, and tetraethyl orthosilicate as precursors and urea as a precipitating agent, followed by hydrothermal reaction, filtration, drying, calcination, and hydrogen reduction.
[0009] A preparation method of a catalyst for the preparation of crotonaldehyde from ethanol dehydrogenation, comprising the following steps:
[0010] (1) Mix copper nitrate, additive metal nitrate, ethanol, deionized water, and tetraethyl orthosilicate in the appropriate proportions, and stir at room temperature for 20-40 min to obtain a uniform mixture;
[0011] (2) Add urea to the mixture obtained in step (1) and continue stirring at room temperature for 20-40 min to form a stable precursor sol system;
[0012] (3) Load the sol system of step (2) into a reaction kettle and maintain a constant temperature of 100-150°C for 18-48 h;
[0013] (4) cooling the reactor to room temperature, filtering the gel-like product, washing the obtained solid with deionized water until the filtrate is neutral, then drying at 100-150 DEG C, and calcining in an air atmosphere at 500-600 DEG C for 4-6 h to obtain a catalyst precursor;
[0014] (5) reducing the catalyst precursor in a hydrogen-nitrogen mixed atmosphere (H2 / N2=0.2-1) at 250-350 DEG C for 3-5 h to obtain the target catalyst.
[0015] Preferably, the auxiliary metal nitrate is one or more of chromium nitrate nine hydrate, cerium nitrate six hydrate, lanthanum nitrate six hydrate, zirconium nitrate five hydrate or zinc nitrate six hydrate.
[0016] Preferably, in step (1), the SiO2 carrier is added in an amount adjusted by the amount of tetraethyl orthosilicate, the mass ratio of the nitrate to water is 1:15-200, and the volume ratio of ethanol to tetraethyl orthosilicate is 2:1-10.
[0017] Preferably, in step (2), the amount of urea added is 1-3 times the total molar amount of metal ions.
[0018] Preferably, in step (4), the temperature is raised to 400 DEG C at 10-15 DEG C and held for 0.5-1.5 h, and then heated to 500-600 DEG C and calcined for 3-5 h.
[0019] The application of the catalyst for preparing crotonaldehyde by dehydrogenation of ethanol, when the catalyst is used in the preparation of crotonaldehyde by a dehydrogenation-condensation-isomerization series reaction, the reaction is carried out in a fixed bed reactor, the reaction temperature is 290-360 DEG C, the mass space velocity of ethanol is 0.5-1.5 h -1 , the reaction pressure is normal pressure, and the raw material is anhydrous ethanol or aqueous ethanol.
[0020] Preferably, the ethanol conversion rate is 55-85%, and the crotonaldehyde selectivity is 65-85%.
[0021] Preferably, after the reaction is continuously operated for 500 h, the catalyst is subjected to regeneration treatment, the regeneration treatment is calcination in an air atmosphere at 300-500 DEG C for 2-3 h, and then hydrogen reduction at 250-350 DEG C for 2-3 h.
[0022] The application has the following beneficial effects:
[0023] 1. One-step high-efficiency conversion: the Cu-M / SiO2 (M is an auxiliary agent) catalyst designed in the application ingeniously integrates the dehydrogenation active center (Cu) and the acid / basic sites (regulated by the auxiliary agent and the carrier) capable of promoting condensation and dehydration reactions, successfully realizes one-step conversion of ethanol into crotonaldehyde in a single reactor, greatly simplifies the process flow, and reduces equipment investment and operating costs.
[0024] 2. Ingenious catalyst design: Copper is used as the dehydrogenation core to ensure the efficient conversion of ethanol to acetaldehyde in the first step; the introduction of Cr, Ce and other additives not only improves the dispersion of copper and inhibits its sintering, but also interacts with the support SiO2 to adjust the acidity and basicity of the catalyst surface, creating active sites that are conducive to the aldol condensation and dehydration steps, thus achieving synergistic catalysis of the three-step reaction.
[0025] 3. Green and economical raw materials: Using widely available and renewable ethanol as the raw material avoids dependence on petroleum-based ethylene or acetaldehyde, in line with the requirements of green chemistry and sustainable development.
[0026] 4. Mild reaction conditions and high selectivity: The reaction is carried out at atmospheric pressure and a moderate temperature (290-360℃). Under optimized conditions, the selectivity of crotonaldehyde can be as high as 85%, significantly higher than traditional multi-step processes and existing one-step method technologies, with fewer by-products and simple product separation and purification.
[0027] 5. Good catalyst stability and reusability: The catalyst prepared by the sol-gel and hydrothermal combination method has uniform dispersion of active components and strong combination with the support, showing good resistance to sintering and carbon deposition. When the activity decreases, it can be regenerated by a simple calcination-reduction process, with a long service life and suitable for industrial continuous production.
[0028] Of course, implementing any product of the present application does not necessarily require achieving all the advantages described above at the same time. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0030] Example 1: Preparation and application of catalyst Cat-1 (Cu-Cr / SiO2)
[0031] 5.7g of copper nitrate trihydrate (containing about 1.5g of Cu) and 3.85g of chromium nitrate nonahydrate (containing about 0.5g of Cr) were weighed as metal precursors and dissolved in a mixed solvent of 80mL of anhydrous ethanol and 150mL of deionized water. While stirring, 35.5g of tetraethyl orthosilicate was added, and the stirring was continued at room temperature for 30min. Then, 15g of urea (about 2 times the total moles of metal ions) was added, and the stirring was continued for another 30min to form a uniform sol.
[0032] The sol was transferred into a 200 mL Teflon-lined stainless steel autoclave and reacted at 120 °C for 24 h in an oven. After the reaction, the reactor was allowed to cool to room temperature naturally and the solid gel was separated by suction filtration and washed with deionized water until the filtrate was neutral. The obtained solid was dried in an oven at 120 °C overnight (about 12 h). Subsequently, the dried powder was placed in a muffle furnace and heated to 550 °C at a rate of 2 °C / min under air atmosphere and calcined at this temperature for 5 h to obtain the catalyst precursor. The Cu loading of the catalyst was about 15 wt% and the Cr loading was about 5 wt%, with the rest being SiO2.
[0033] The 2.0 g of catalyst precursor was loaded into a fixed-bed reactor and reduced at 300 °C for 4 h under a hydrogen atmosphere (flow rate 40 mL / min). The reaction temperature was raised to 320 °C and the ethanol conversion was carried out at atmospheric pressure with an ethanol mass hourly space velocity (MHV) of 1.0 h -1 ; the ethanol conversion was 78.5% and the crotonaldehyde selectivity was 76.2%.
[0034] Example 2: Preparation of catalyst Cat-2 (Cu-Ce / SiO2)
[0035] The 2.0 g of catalyst precursor was loaded into a fixed-bed reactor and reduced at 300 °C for 4 h under a hydrogen atmosphere (flow rate 40 mL / min). The reaction temperature was raised to 320 °C and the ethanol conversion was carried out at atmospheric pressure with an ethanol mass hourly space velocity (MHV) of 1.0 h -1 ; the ethanol conversion was 78.5% and the crotonaldehyde selectivity was 76.2%.
[0036] Example 3: Preparation of catalyst Cat-3 (Cu-Zn / SiO2)
[0037] The 2.0 g of catalyst precursor was loaded into a fixed-bed reactor and reduced at 300 °C for 4 h under a hydrogen atmosphere (flow rate 40 mL / min). The reaction temperature was raised to 320 °C and the ethanol conversion was carried out at atmospheric pressure with an ethanol mass hourly space velocity (MHV) of 1.0 h -1 ; the ethanol conversion was 78.5% and the crotonaldehyde selectivity was 76.2%.
[0038] Example 4: Preparation of catalyst Cat-4 (Cu-La / SiO2)
[0039] The 2.0 g of catalyst precursor was loaded into a fixed-bed reactor and reduced at 300 °C for 4 h under a hydrogen atmosphere (flow rate 40 mL / min). The reaction temperature was raised to 320 °C and the ethanol conversion was carried out at atmospheric pressure with an ethanol mass hourly space velocity (MHV) of 1.0 h -1 ; the ethanol conversion was 78.5% and the crotonaldehyde selectivity was 76.2%.
[0040] Example 5: Preparation of catalyst Cat-5 (low Cu loading)
[0041] Take 3.8 g of copper nitrate trihydrate (Cu loading target 10%), 9 g of zinc nitrate hexahydrate (Zn loading target 2%), and accordingly reduce the amount of nitrate salt, and the remaining steps are the same as in Example 1. Catalyst Cat-5 is obtained. The reaction conditions are the same as in Example 1, and the ethanol conversion rate is 58.9%, and the crotonaldehyde selectivity is 68.4%.
[0042] Example 6: Preparation of catalyst Cat-6 (high Cu loading)
[0043] Take 9.5 g of copper nitrate trihydrate (Cu loading target 25%), 9 g of zinc nitrate hexahydrate (Zn loading target 2%), and the remaining steps are the same as in Example 1. Catalyst Cat-6 is obtained. The reaction conditions are the same as in Example 1, and the ethanol conversion rate is 84.2%, and the crotonaldehyde selectivity is 75.8%.
[0044] Example 7: Preparation of catalyst Cat-7 (change of hydrothermal temperature)
[0045] The preparation steps are exactly the same as in Example 1, the only difference is that the hydrothermal reaction temperature is changed to 150°C, and the reaction time is 18h. Catalyst Cat-7 is obtained. The reaction conditions are the same as in Example 1, and the ethanol conversion rate is 75.8%, and the crotonaldehyde selectivity is 74.1%.
[0046] Example 8: Preparation of catalyst Cat-8 (change of additive combination)
[0047] Take 5.7 g of copper nitrate trihydrate, 9 g of zinc nitrate hexahydrate (Zn loading target 2%), and 4.87 g of cerium nitrate hexahydrate (Ce loading target 1.5%), i.e. Zn and Ce are used as composite additives, and the remaining steps are the same as in Example 1. Catalyst Cat-8 is obtained. The reaction conditions are the same as in Example 1, and the ethanol conversion rate is 79.5%, and the crotonaldehyde selectivity is 78.9%.
[0048] Example 9: Catalyst Cat-9 (using 95% ethanol as raw material)
[0049] The same catalyst Cat-1 as in Example 1 is used, but when evaluating the performance, the feedstock is changed from anhydrous ethanol to 95% ethanol (containing 5% water). The reaction conditions are the same as in Example 1, and the ethanol conversion rate is 76.1%, and the crotonaldehyde selectivity is 74.5%.
[0050] Comparative Example 1: Preparation of catalyst C-1 (Cu / SiO2, no additives)
[0051] Take 5.7 g of copper nitrate trihydrate, and do not add any additive metal nitrate, and the remaining steps are the same as in Example 1. Catalyst C-1 is obtained, in which the Cu loading is about 15wt%. The reaction conditions are the same as in Example 1, and the ethanol conversion rate is 65.2%, and the crotonaldehyde selectivity is 58.7%.
[0052] Comparative Example 2: Catalyst C-2 (prepared by physical mixing method)
[0053] 20%Cu / SiO2and 5%Cr / SiO2catalysts were prepared by impregnation method respectively, and then were physically mixed in a mass ratio of 4:1 to make their total composition similar to that of Cat-1. The reaction conditions were the same as in Example 1, and the ethanol conversion rate was 61.5% and the crotonaldehyde selectivity was 52.3%.
[0054] I. Catalytic performance
[0055] The ethanol-to-crotonaldehyde reaction performance of the catalysts prepared in Examples 1-9 and Comparative Examples 1 and 2 is shown in Table 1 below.
[0056] Table 1. Ethanol-to-crotonaldehyde reaction performance of different catalysts
[0057] Note: The hydrothermal condition of Cat-7 is 150℃ / 18h, and the raw material of Cat-9 is 95% ethanol
[0058] As can be seen from the data in Table 1, the selectivity of crotonaldehyde of all the catalysts containing promoters (Cr, Ce, Zn, La) (Cat-1 to Cat-4, Cat-8) is significantly higher than that of Comparative Example C-1 without promoters (58.7%), generally reaching more than 70%. This indicates that the promoters effectively modify the surface properties of the catalysts and promote the conversion of the acetaldehyde intermediate to crotonaldehyde.
[0059] As can be seen from Comparative Examples 3, 5 and 6, as the Cu loading increases from 10% to 25%, the ethanol conversion rate significantly increases (58.9%→81.6%→84.2%), but too high Cu loading (25%) can cause some condensation / dehydration sites to be covered, resulting in a slight decrease in crotonaldehyde selectivity (from 80.5% to 75.8%). A Cu loading of 20% shows the best balance of activity and selectivity in this system.
[0060] Example 7 (Cat-7) still has good catalytic performance by increasing the hydrothermal temperature, indicating that the preparation method of the present application has certain operational flexibility. Example 8 (Cat-8) uses Zn-Ce composite promoters and has better performance than Cat-2 with single Ce promoter, showing that there may be a synergistic effect between the promoters.
[0061] Example 9 (Cat-9) shows that using 95% ethanol, which is cheaper, as the raw material, the catalyst still maintains excellent performance, only slightly lower in activity and selectivity than when using anhydrous ethanol, showing good prospects for industrial application.
[0062] Comparative Example 2 (C-2) was prepared by physical mixing method, which has much lower performance than Cat-1 prepared by sol-gel / hydrothermal one-pot method. This proves that the preparation method adopted in the present application can make the active component (Cu) and the adjuvant (Cr) uniformly dispersed and closely contacted at nanoscale, thereby forming a highly efficient synergistic catalytic system, which cannot be achieved by physical mixing method.
[0063] II. Stability and regeneration test
[0064] The catalyst Cat-1 in Example 1 was continuously operated at 320℃, ethanol mass space velocity 1.0 h -1 under normal pressure for 500h, and samples were periodically analyzed:
[0065] 0h of operation: ethanol conversion rate 78.5%, crotyl aldehyde selectivity 76.2%;
[0066] 100h of operation: ethanol conversion rate 78.2%, crotyl aldehyde selectivity 75.9%;
[0067] 300h of operation: ethanol conversion rate 77.8%, crotyl aldehyde selectivity 75.5%;
[0068] 500h of operation: ethanol conversion rate 77.5%, crotyl aldehyde selectivity 75.2%.
[0069] After 500h of operation, Cat-1 was subjected to regeneration treatment: stop feeding ethanol, and cool down under nitrogen protection. Then switch to air, and calcine at 400℃ for 3h, and then switch to hydrogen, and reduce at 300℃ for 3h. The performance of the regenerated catalyst is restored to more than 96% of the initial activity and selectivity, indicating that the catalyst has good regeneration performance and service life.
[0070] In the description of the present specification, the description referring to the terms "one embodiment", "an example", "a specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0071] The basic principles, main features and advantages of the present application are shown and described above. It should be understood by those skilled in the art that the present application is not limited by the above examples, and the above examples and descriptions in the specification are only to illustrate the principles of the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application.
Claims
1. A catalyst for the production of crotonaldehyde by the dehydrogenation of ethanol, characterized in that, The catalyst comprises a SiO2 carrier, an active component and an auxiliary metal loaded on the SiO2 carrier, the active component is copper, the auxiliary metal is one or more of chromium, cerium, lanthanum, zirconium and zinc, the mass percentage of the SiO2 carrier is 70-89.5%, the mass percentage of the active component is 10-25%, and the mass percentage of the auxiliary metal is 0.5-5%, the catalyst is prepared by a sol-gel method, copper nitrate, auxiliary metal nitrate and tetraethyl orthosilicate are used as precursors, and urea is used as a precipitant, and the catalyst is obtained through hydrothermal reaction, filtration, drying, calcination and hydrogen reduction.
2. The method for preparing the catalyst for the dehydrogenation of ethanol to crotonaldehyde as described in claim 1, characterized in that, The method comprises the following steps: (1) mixing copper nitrate, auxiliary metal nitrate, ethanol, deionized water and tetraethyl orthosilicate in a proportion, stirring at room temperature for 20-40 min to obtain a uniform mixture; (2) adding urea to the mixture obtained in step (1) and continuing to stir at room temperature for 20-40 min to form a stable precursor sol system; (3) loading the sol system of step (2) into a reaction kettle and reacting at a constant temperature of 100-150 ℃ for 18-48 h; (4) cooling the reaction kettle to room temperature, filtering the gel product, washing the obtained solid with deionized water until the filtrate is neutral, then drying at 100-150 ℃, and calcining in an air atmosphere at 500-600 ℃ for 4-6 h to obtain a catalyst precursor; (5) placing the catalyst precursor in a hydrogen-nitrogen mixed atmosphere, wherein H2 / N2 is 0.2-1, and reducing at 250-350 ℃ for 3-5 h to obtain the target catalyst.
3. The method of claim 2, wherein the catalyst is prepared by the steps of: (a) preparing a solution of a transition metal compound in a solvent; (b) adding a reducing agent to the solution; (c) adding a base to the solution; (d) adding a ligand to the solution; and (e) recovering the catalyst. The auxiliary metal nitrate is one or more of chromium nitrate nonahydrate, cerium nitrate hexahydrate, lanthanum nitrate hexahydrate, zirconium nitrate pentahydrate or zinc nitrate hexahydrate.
4. The method for preparing the catalyst for the dehydrogenation of ethanol to crotonaldehyde according to claim 2, characterized in that, In step (1), the amount of SiO2 carrier is adjusted by the amount of tetraethyl orthosilicate, the mass ratio of nitrate to water is 1:15-200, and the volume ratio of ethanol to tetraethyl orthosilicate is 2:1-10.
5. The method for preparing the catalyst for the dehydrogenation of ethanol to crotonaldehyde according to claim 2, characterized in that, In step (2), the amount of urea added is 1-3 times the total molar amount of metal ions.
6. The method for preparing the catalyst for the dehydrogenation of ethanol to crotonaldehyde according to claim 2, characterized in that, In step (4), the temperature is increased to 400 ℃ at a rate of 10-15 ℃ / h, maintained for 0.5-1.5 h, and then heated to 500-600 ℃ for calcination for 3-5 h.
7. Use of the catalyst for preparing crotonaldehyde by ethanol dehydrogenation according to claim 1, characterized in that, When the catalyst is used in the preparation of crotonaldehyde by a dehydrogenation-condensation-isomerization series reaction, the reaction is carried out in a fixed bed reactor, the reaction temperature is 290-360℃, the mass space velocity of ethanol is 0.5-1.5h -1 -1, the reaction pressure is normal pressure, and the raw material is anhydrous ethanol or aqueous ethanol.
8. Use of the catalyst for preparing crotonaldehyde by ethanol dehydrogenation according to claim 7, characterized in that, The ethanol conversion rate is 55-85%, and the crotonaldehyde selectivity is 65-85%.
9. The use of the catalyst for preparing crotonaldehyde by ethanol dehydrogenation according to claim 7, characterized in that, After the reaction is continuously operated for 500 h, the catalyst is subjected to a regeneration treatment, which comprises calcining in an air atmosphere at 300-500 ℃ for 2-3 h, and then reducing in hydrogen at 250-350 ℃ for 2-3 h.
Citation Information
Patent Citations
Method for preparing acetaldehyde through ethanol dehydrogenation
CN116162019A